Measuring Butt Log and Middle Log Volume of Eucalyptus Camaldulensis Using Different Methods in Erbil Province - Ameer Abdulazeez Abdulla; Mohammed Hadayat Obeyed (Zanco Journal of Pure and Applied Sciences, 2022)
The volume of each butt log and middle log of an individual tree at a 5-meter log length was calculated by using five different formulas (Newton`s, Smalian`s, Huber`s, Hossfeld`s, and Centroid method). The volume of the butt logs and middle logs was compared to the real volume (control), which was calculated by aggregating the volume measurements at (0.5) meters using Newton's method. Measurements were taken from 50 trees of (Eucalyptus camaldulensis) planted in Al-Khabat area in Erbil governorate. The sampled trees presented diameter at breast height (DBH) ranged from 30.2 to 75.6 cm and total tree height range from 13 to 27 m. The result showed that Newton`s formula was superior to all other formulas for estimating butt log volume of eucalyptus tree species plantation and Smalian`s formula was less accurate than other formulas. On the other hand, the centroid method was superior to all other formulas for estimating the middle log volume of eucalyptus tree species in the district of khabat in Erbil province. Moreover, the Hossfeld formula was less accurate than other formulas.